Sensitivity Analysis of the Model for Determining the Impacts of Child Labour, Vagrancy, and Ineffective-Almajiri-Mentorship Factors on Schooling in Nigeria - David, Ogwumu O.; Ebenezer, Ubanede; W, Yavala Deboorah (Darul Yasin Al Sys, 2024)
This research is concerned with the modelling of factors influencing the schooling environment in Nigeria, with a specific focus on the impact of child labour, vagrancy, and ineffective Almajiri mentorship. Employing epidemiological approaches within the framework of endemic modeling, the study treated schooling-disruption as an epidemic situation that needs urgent attention using a four compartmental Sl - Cl- Vg - Am modelling structure. Where: Sl = School-learning, Cl = Child labour, Vg = Vagrancy and Am = Almajiri-mentorship. Hence, by unraveling the interconnectivity dynamics between these highlighted social issues that affect schooling in Nigeria and their impacts on education, this research aims at providing valuable insight for policy makers and educators to develop targeted interventions. The Sensitivity analysis of the model on the other hand, provides insight into the varying impact of different parameters on the schooling outcomes, projecting which of the model's parameters is most sensitive or not. However, from the sensitivity report of the model, the most sensitive model parameter is the Progression rate of learners from vagrancy compartment to Almajiri-mentorship compartment ( ). Hence the decision makers ought to discourage children’s homelessness which eventually leads to a strange and unhealthy movement to the inefficient Almajiri-mentorship. The law makers should enact laws which must compel every religions mentorship to combine the official schooling dynamics with the orthodox, traditional and religious children mentorship. Furthermore, based on this research findings, the study recommends a comprehensive implementation of strategies that address the root causes of schooling-disruption outcomes in Nigeria.